Implementation of Fisher-Yates Shuffle Algorithm in National Examination Simulation Applications Based on Website as a Student Learning Means - Lutfi, Mohamad Anwari; Widodo, Tri (SENATIK STT Adisutjipto, 2018)
National Examination (UN) is one of the mandatory requirements that must be passed by students both elementary, junior high, or high school / vocational level to be able to continue to a higher level of education. Students will learn as best they can to pass the National Examination. Therefore researchers are interested in developing a National Examination (UN) simulation application that can be accessed at any time using a computer and internet network so that it can be an alternative means of student learning. This system also implements the Fisher-Yates Shuffle Algorithm Â as a randomization technique on exam questions so that the questions done by students will always be different and varied. This application can be tested in accordance with the design and can be a means of learning or try-out for students who will take the UN